Beyond the fingerstick – Empowering pregnancy with continuous glucose monitoring - Saha, Anjana (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
The optimized control of diabetes during pregnancy is both challenging and essential. The risks associated with uncontrolled diabetes in pregnancy include congenital anomalies, stillbirth and miscarriage, macrosomia. CGM devices utilize waterproof, self-administered subcutaneous sensors to measure interstitial fluid glucose levels continuously. Its emergence has revolutionized the management of diabetes in pregnancy; its use has demonstrated improvements in glycemic control with respect to both hyperglycemic and hypoglycemic events, as well as reported benefits to quality of life. This article focuses on the role of continuous glucose monitoring (CGM) in pregnancy, assessing the evidence available and providing an update on current guidance. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S23]